Pengaruh Jam Kerja Dan Tenaga Kerja Terhadap Pendapatan Usaha Mikro Yang Di Moderasi Oleh Kur - Irpan Saputra; Edi Irawan (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
Micro businesses are businesses that are in great demand among the Indonesian people. Apart from requiring relatively small capital, micro businesses are also one of the businesses that were able to survive in the face of the 1998 monetary crisis. This research aims to see the effect of working hours and labor which are moderated by the People's Business Credit (KUR). ) dtowards Micro Business income. This research uses a quantitative and associative research approach by collecting primary data using questionnaires from people who have micro businesses in Moyo village, Moyo Hilir sub-district, Sumbawa regency. The data analysis method used is the Moderated Regression Analysis (MRA) data analysis method. The results of the research show that working hours and labor and labor influence the income of Micro Businesses in Moyo village by 52% before the People's Business Credit (KUR) moderation. 80%. So that People's Business Credit Strengthens the Influence on Micro Business Income. Then the results of this research also show that working hours have a positive effect on micro business income and labor has a positive effect on micro business income in Moyo Village, Moyo Hilir District, Sumbawa Regency.